2017
DOI: 10.1161/circulationaha.116.024470
|View full text |Cite
|
Sign up to set email alerts
|

Sheet-Like Remodeling of the Transverse Tubular System in Human Heart Failure Impairs Excitation-Contraction Coupling and Functional Recovery by Mechanical Unloading

Abstract: Background Cardiac recovery in response to mechanical unloading by left ventricular assist devices (LVADs) has been demonstrated in subgroups of chronic heart failure (HF) patients. Hallmarks of HF are depletion and disorganization of the transverse tubular system (t-system) in cardiomyocytes. Here, we investigated remodeling of the t-system in human end-stage HF and its role in cardiac recovery. Methods Left ventricular biopsies were obtained from 5 donors (CTRL) and 26 chronic HF patients undergoing implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 52 publications
(67 reference statements)
4
89
1
Order By: Relevance
“…These “t-sheets” were dilated in longitudinal myocyte direction and still connected to the outer sarcolemma (Fig. 2F), showing high similarity to the phenotype observed in human end-stage heart failure (Seidel et al, 2017). These results support that WGA reliably stains the t-system in normal and remodeled rabbit myocytes.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…These “t-sheets” were dilated in longitudinal myocyte direction and still connected to the outer sarcolemma (Fig. 2F), showing high similarity to the phenotype observed in human end-stage heart failure (Seidel et al, 2017). These results support that WGA reliably stains the t-system in normal and remodeled rabbit myocytes.…”
Section: Resultssupporting
confidence: 59%
“…While t-system remodeling in rodents leads mainly to disorganized orientation and increased axial components (Chen et al, 2012; Wagner et al, 2012; Wei et al, 2010), the predominant remodeling in humans and larger mammals, such as canine or pig, is loss and dilation of t-tubules (Biesmans et al, 2011; Crossman et al, 2017; Kostin et al, 1998; Sachse et al, 2012). We recently described the 3D structure of a sheet-like remodeled t-tubules (t-sheets) in humans, which is symptomatic for end-stage heart failure (Seidel et al, 2017). It still remains unclear if t-sheets are also present in animal models of heart failure, but most likely not in mice or rats because these species have already been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…T-tubule remodeling and the resultant abnormal calcium transients are central to the pathophysiology of HF [13,17,[37][38][39][40][41][42][43][44][45]. Our groups and others have identified that t-tubule remodeling can be a consequence of reduced cBIN1 [9,10].…”
Section: Cbin1 Based Cs Is a Marker Of Biochemical Health Of Cardiomymentioning
confidence: 90%